Potential Technosignature from Anomalously Low Deuterium/Hydrogen in Planetary Water Depleted by Nuclear Fusion Technology - David C. Catling; Joshua Krissansen-Totton; Tyler D. Robinson (The Astrophysical Journal)
Deuterium–deuterium (DD) fusion is viewed as an ideal energy source for humanity in the far future, given a vast seawater supply of D. Here, we consider long-lived, extraterrestrial, technological societies that develop DD fusion. If such a society persisted over geologic timescales, oceanic deuterium would diminish. For an ocean mass and initial deuterium/hydrogen (D/H) ratio that were Earth-like, fusion power use of only ∼10 times that projected for humankind next century would deplete the D/H ratio in ∼(a few) ×10 ^8 yr to values below that of the local interstellar medium (ISM). Ocean masses of a few percent of Earth’s would reach an anomalously low D/H in ∼10 ^6 –10 ^7 yr. The timescale shortens with greater energy consumption, smaller oceans, or lower initial D/H. Here, we suggest that anomalous D/H in planetary water below local ISM values of ∼16 × 10 ^−6 (set by Big Bang nucleosynthesis plus deuterium loss onto dust or small admixtures of deuterium-poor stellar material) may be a technosignature. Unlike SETI using radio signals, anomalous D/H would persist for eons, even if civilizations perished or relocated. We discuss the wavelengths of strong absorption features for detecting D/H anomalies in atmospheric water vapor. These are vibrational O–D stretching at 3.7 μ m in transmission spectroscopy of Earth-like worlds, ∼1.5 μ m (in the wings of the 1.4 μ m water band) in the shorter near-infrared for direct imaging by the Habitable Worlds Observatory, and ∼7.5-8 μ m (in the wings of the broad 6.3 μ m bending vibration of water) for concepts like the Large Interferometer for Exoplanets.